Mass Communication Cannot Be Separated From Ethical Problems - M. Yoserizal Saragih; Ali Imran Harahap (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2020)
This paper deals with mass communication cannot be separated from ethical problems. One of our goals in studying the science of communication lies in the dimension of ethical communication. Ethics can be defined as a set of moral principles or values. Ethical standards can differ from one discipline to another. In the discipline of communication, a set of communication ethics has been adopted into various communication contexts and communication fields, some of which we have understood together are business communication ethics, interpersonal communication ethics, and public relations ethics. Mass communication ethics is a moral philosophy that deals with the obligations of the press and about the judgments of the good press and the bad press or the right press and the wrong press. Each mass media has its own code of ethics because indeed each type of mass media has its own character or characteristics, so we know that in this world there are print media journalistic ethics, journalistic code of ethics, radio, and television journalistic code of ethics.